Wideband Active RISs: Architecture, Modeling, and Beamforming Design - Zhang, Jida; Li, Zhiyi; Zhang, Zijian (IEEE communications letters, 2023)
Reconfigurable intelligent surfaces (RISs) have become a candidate for future 6G networks. The concept of active RISs has been recently proposed to overcome the multiplicative fading of RIS aided reflected links. However, due to the frequency-selective channels, the narrowband active RISs suffer from a large performance loss in wideband scenarios. To address this issue, in this letter, we propose wideband active RISs, including their architecture, modeling, and beamforming design. Specifically, the key idea of wideband active RISs is to divide all subcarriers into several groups and the subcarriers in each group are configured by a single amplifying and phase-shift circuit. Based on this architecture, we derive the frequency-domain channel model and noise model of a wideband active RIS aided communication system. Then, we formulate a beamforming design problem for sum-rate maximization, and a joint transmit precoding and reflect beamforming algorithm is proposed to solve the problem. Simulation results verify the significant performance improvement of the proposed wideband RISs in wideband scenarios.